THE USE OF GOLDEN SNAIL MEAL TO ENRICH BACILLUS THURINGIENSIS CULTURE MEDIA AND ITS EFFECT ON THE BACTERIAL TOXICITY AGAINST SPODOPTERA LITURA - Pujiastuti, Yulia; Masyitah, Siti; Dirgahayu, Sarah; Hadikusuma, Suparman Surya; ., Effendy (Universitas Lampung, 2018)
The use of golden snail meal to enrich Bacillus thuringiensis culture media and its effect on the bacterial toxicity against spodoptera litura. Bacillus thuringiensis is an entomopathogenic bacterium producing spore and protein at sporulation. There has been limited research on using golden snail as protein resource to enrich bacterial culture media. This research was aimed at studying bacterial cell/spore production in culture media made from coconut water media and liquid waste of tofu industry (tofu whey) enriched with golden snail meal (GSM), as well as its toxicity against Spodoptera litura. The research was conducted in the Laboratory of Entomology, Department of Plant Protection, Faculty of Agriculture, Sriwijaya University, from June to September 2017. The experiment was arranged in a Factorial Completely Randomized Design (FCRD) with two factors and three replications. The first factor was the addition of GSM (0, 5, 9, 13 and 17 g) and the second was storage longevity (0, 1, and 2 months). Number of test insect (third instar of S. litura) was 30 larvae per treatment. Parameter observed were spore density, larval mortality, and symptom of infected larvae. The results showed that B. thuringiensis cultured in culture media enriched with 13 g golden snail meal produced the highest spore density, amounted to 14.14 x 107spores/ml and caused larval mortality up to 86.67%. After one and two month storage treatments, the spore density in the cultures reduced to 2.51 x 107 and 1.49 x 107 spores/ml, respectively. There was a tendency of reduction in spore density under longer storage of the culture. Survived larvae developed abnormally, failed to transform to pupa or imago.